Информация, значение и смысл в языковых процессах сознания [Information, meaning and sense in the linguistic process of consciousness] - Barishnikov, Pavel (Rivista Italiana di Filosofia del Linguaggio, 2012)
In this article the linguistic processes of consciousness are discussed at the informational and semantic levels. The key question is devoted to the distinction between the information, meaning and sense in the physical, logico-semantic and historic levels of brain and consciousness. The principal point runs that the human linguistic process of sense producing takes the variety and indistinctness in the cultural presupposition. The modern theories of philosophy of mind relying on the theories of Soviet psychological school propose some new solutions in the pragmatic questions of the semantic noncomputability. In this review we will try to justify the dualistic correlation between the cultural base and the communicative semantic process